Assessment of the apical part of the roots after their instrumentation by different endodontic systems - A. V. Mitronin; V. V. Vedmitskaya; L. A. Khromova (LLC "Endo Press", 2020)
Relevance. The goal of root canal instrumentation is elimination of bacteria and tissues and enlargement of canal diameter for optimal obturation. The aim of this study was to conduct a comparative analysis of most commonly used among Russian practitioners rotary systems for root canal instrumentation.Aim. To determine the causes of an apical crack formation.Materials and methods. Recently extracted teeth with one root were used in the research. They were divided into 4 groups: instrumented with ProTaper (Dentsply Maillefer), Mtwo (VDW), ProFile (Dentsply Maillefer) and hand stainless steel files.Results. No cracks were observed after root canal instrumentation with hand files. Instrumentation with rotary nickeltitanium files caused apical cracks formation. The biggest amount of cracks was caused by ProTaper files (Dentsply Maillefer), the least amount of cracks was caused by Mtwo files (WDW).